PRINCIPLES OF INTERNATIONAL LAW OF HUMAN RIGHTS APPLICABLE IN A STATE OF EMERGENCY COVID-19 AND THE USE OF FORCE BY POLICE PERSONNEL - Peruana de Derecho Internacional, Sociedad (2020)
It is analyzed whether the measures adopted by Peru to face the COVID19 emergency observes the international human rights standards and principles contained in the Guidance on the use of force by law-enforcement personnel in time of COVID-19 emergency adopted by the United Nations Special Rapporteur on Extrajudicial, Summary or Arbitrary Killings: States of emergency are exceptional and strictly limited, the right to life is non-derogable, law-enforcement measures should be guided by the principles of legality, necessity, proportionality, precaution and non-discrimination, emergency measures should not increase the risk of vulnerable groups, and the police should opérate under the principles of discussion, instruction, consultation and community engagement, considering that such contexts have historically led to an increase in violence by the State, mainly against vulnerable people by law enforcement personnel.